2002
DOI: 10.1177/0021998302036007614
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness Degradation of FRP Strengthened RC Beams Subjected to Hygrothermal and Aging Attacks

Abstract: The past decade has witnessed an ever increasing interest in strengthening, repairing, retrofitting, and upgrading of deteriorated concrete structures using fiber reinforced plastics (FRP). Enhanced load carrying capacity by FRP strengthening has been observed by a large number of researchers through experiments at ambient environments. In a harsh environment, however, FRP will degrade. This may result in structural degradation of FRP strengthened concrete members. The possible structural degradation has becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…The presence of moisture (100% humidity) slightly improved cohesive strength compared to the 0% humidity samples while the differences in cohesive strength at each humidity reduced with increasing cycle numbers. When submerged in water, the strengths were the lowest with the largest coefficient of variation, which could be partially attributed to the higher moisture uptake by the resin and, consequently, plasticization [6,37]. The dry air (0% relative humidity) exposure at 100°C showed a slight increase in strength over time, which is consistent with Elarbi's results [16] but is yet to be understood.…”
Section: Control Samplessupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of moisture (100% humidity) slightly improved cohesive strength compared to the 0% humidity samples while the differences in cohesive strength at each humidity reduced with increasing cycle numbers. When submerged in water, the strengths were the lowest with the largest coefficient of variation, which could be partially attributed to the higher moisture uptake by the resin and, consequently, plasticization [6,37]. The dry air (0% relative humidity) exposure at 100°C showed a slight increase in strength over time, which is consistent with Elarbi's results [16] but is yet to be understood.…”
Section: Control Samplessupporting
confidence: 83%
“…Although the short term performance of FRP sheets has been satisfactory, the long term performance of FRP bonded concrete structures are still uncertain. Environmental factors have been reported to have negative effects on the durability performance of FRP [5,6]. Environmental conditions may involve temperature, humidity, salt water, chemicals, and freeze-thaw cycles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various environmental conditions such as freeze-thaw cycles, wet-dry cycles, combined environmental cycles, boiling water and UV radiation, hydrothermal ageing under constant temperature and humidity, and dry heat were applied by Chajes et al (1995), Toutanji and Gó mez (1997), Myers et al (2001), Li et al (2002) and Grace (2004) to investigate the long term performance of FRP strengthened concrete beams in terms of ultimate strength and/or stiffness of beams. Chajes et al (1995) reported wet-dry cycles as slightly more severe than freeze thaw cycles (Calcium Chloride was solution was used in both cases) and graphite reinforced beams as the most durable compared to aramid and E-glass reinforced beams (36 % drop in strength was observed for aramid and E-glass reinforced beams due to wet-dry cycles).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] The research results showed that the environmental temperature cannot be ignored as the most common influencing factor. [7][8][9] The research results showed that the environmental temperature cannot be ignored as the most common influencing factor.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the influence of environments on fatigue performance and durability of the RC structures strengthened with FRP has attracted more and more attention in civil engineering field. [7][8][9] The research results showed that the environmental temperature cannot be ignored as the most common influencing factor. Adimi et al 7 found out the fatigue lives of concrete beams strengthened with carbon fibre-reinforced polymer (CFRP) bars Nomenclature: D, Palmgren-Miner accumulated damage; D c , Palmgren-Miner accumulated critical damage; N, fatigue life; N m , average fatigue life; n i , loading cycles under the ith stress level; ΔP mean , average loading amplitude of the vehicle random loading spectrum; P max , average peak load of the vehicle random loading spectrum; P u , ultimate load-bearing capacity of the strengthened beam; S R , loading level of the vehicle random loading spectrum were obviously decreased as temperature was increased from room temperature to 40°C.…”
Section: Introductionmentioning
confidence: 99%